Model bisnis pengembangan produk unggulan mutiara di Kelurahan Palabusa Kota Baubau - Nadia, La Ode Abdul Rajab; Salwiyah; Piliana, Wa Ode; Hamzah, Muhaimin; Afyudi, Bobby (Jurnal Sosial Ekonomi Perikanan, 2024)
Palabusa Village is one of the coastal areas that currently has developed pearl superior products, both on a cultivation and pearl processing scale.  The business has been going on for a long time and tends to experience a decline in investment.  The purpose of the study was to analyze the business model and investment of pearl businesses in Palabusa Village, Baubau City. This research was conducted for 3 months, namely August - November 2023.  The research location is Palabusa Village, Baubau City. Data collection methods were in-depth interviews and PRA activities. The analysis used to determine the level of economic and investment feasibility is the analysis of investment criteria.  Business model analysis based on Assessment of potential partners, especially pearl superior product business actors using the M4P (Making Market Work for the Poor) method. The results of the study are that the mabe mussel cultivation business is very feasible to continue and develop with an R/C value of 1.73 by meeting the criteria that the value is greater than 1. At an interest rate of 13%, the NPV value is Rp13,375,000, the profit of the mabe mussel cultivation business for 5 years of investment life brings a profit of Rp13,375,000. Profits and R/C are large enough to be obtained in the pearl craft business and are very feasible to develop and improve. The value chain of pearl products in Palabusa village is very short, namely cultivators, processors, intermediary traders and end consumers. The business scenario of pearl products involves many parties including the government, private sector, banks/cooperatives, collecting traders/souvenir shops. The conclusion of this study is that the pearl product business in Palabusa Village is very feasible to develop.  Multi-stakeholder involvement strongly supports the pearl product business scenario so that it can increase income and sustainability of community businesses.